Consumer Choicemaking and Choicelessness in Hyperdigital Marketspaces. (March 2021) - Dholakia, Nikhilesh; Darmody, Aron; Zwick, Detlev; Dholakia, Ruby Roy; Fırat, A. Fuat
Technologies, especially Internet-based digital ones, are reshaping choice processes – actual considerations and actions, as well as perceptions of these – in massive, often fundamental, ways. In this paper, our goal is to explore choice processes in general, and especially choice processes in hyperdigital marketspaces (i.e., with massively, pervasively interconnected things) with examples drawn from U.S. macro consumption contexts. We start with a short review of discourses on choice and choicelessness and then shift to the emerging era of technology-shaped choice processes that are especially observable in contemporary hyperdigital marketspaces. For the increasingly large swaths of market segments that consume, indeed live, digitally, we find deft symbolic sublimations and inversions happening, wherein manipulation is perceived as autonomy enhancing.